Mechanical and Failure Criteria of Air-Entrained Concrete under Triaxial Compression Load after Rapid Freeze-Thaw Cycles - Feng-kun Cui; Huai-shuai Shang; Tie-jun Zhao; Guo-xi Fan; Guo-sheng Ren (Advances in Materials Science and Engineering)
The experiment study on the air-entrained concrete of 100 mm cubes under triaxial compression with different intermediate stress ratio α2=σ2D : σ3D was carried out using a hydraulic-servo testing system. The influence of rapid freeze-thaw cycles and intermediate stress ratio on the triaxial compressive strength σ3D was analyzed according to the experimental results, respectively. The experimental results of air-entrained concrete obtained from the study in this paper and the triaxial compression experimental results of plain concrete got through the same triaxial-testing-system were compared and analyzed. The conclusion was that the triaxial compressive strength is greater than the biaxial and uniaxial compressive strength after the same rapid freeze-thaw cycles, and the increased percentage of triaxial compressive strength over biaxial compressive strength or uniaxial compressive strength is dependent on the middle stress. The experimental data is useful for precise analysis of concrete member or concrete structure under the action complex stress state.